Candidate Gene Resequencing in a Large Bicuspid Aortic Valve-Associated Thoracic Aortic Aneurysm Cohort: SMAD6 as an Important Contributor - Gillis, Elisabeth; Kumar, Ajay A.; Luyckx, Ilse; Preuss, Christoph; Cannaerts, Elyssa; van de Beek, Gerarda; Wieschendorf, Björn; Alaerts, Maaike; Bolar, Nikhita; Vandeweyer, Geert; Meester, Josephina; Wünnemann, Florian; et al. (Frontiers in Physiology, 2017)
Bicuspid aortic valve (BAV) is the most common congenital heart defect. Although many BAV patients remain asymptomatic, at least 20% develop thoracic aortic aneurysm (TAA). Historically, BAV-related TAA was considered as a hemodynamic consequences of the valve defect. Multiple lines of evidence currently suggest that genetic determinants contribute to the pathogenesis of both BAV and TAA in affected individuals. Despite high heritability, only very few genes have been linked to BAV and BAV/TAA, such as NOTCH1, SMAD6 and MAT2A. Moreover, they only explain a minority of patients. Other candidate genes have been suggested based on the presence of BAV in knockout mouse models (e.g. GATA5, NOS3) or in syndromic (e.g. TGFBR1/2, TGFB2/3) or non-syndromic (e.g. ACTA2) TAA forms. We hypothesized that rare genetic variants in these genes may be enriched in patients presenting with both BAV and TAA. We performed targeted resequencing of 22 candidate genes using Haloplex target enrichment in a strictly defined BAV/TAA cohort (n=441; BAV in addition to an aortic root or ascendens diameter ≥4.0 cm in adults, or a Z-score ≥3 in children) and in a collection of healthy controls with normal echocardiographic evaluation (n=183). After additional burden analysis in comparison to the Exome Aggregation Consortium database, the strongest candidate susceptibility gene was SMAD6 (p=0.002), with 2.5% (n=11) of BAV/TAA patients harboring causal variants, including two nonsense, one in-frame deletion and two frameshift mutations. All six missense mutations were located in the functionally important MH1 and MH2 domains. In conclusion, we report a significant contribution of SMAD6 mutations to the etiology of the BAV/TAA phenotype.